A Black Sea Belle Epoque Tale. Queen Elisabeta At Evksinograd: The Last Journey to Bulgaria of a Sovereign of Romania (13–16 May 1911) - Florin Anghel (Studia Maritima)
Between 13 and 16 May 1911, the last visit that a sovereign of Romania made to the territory of Bulgaria took place. Queen Elisabeta of Romania was invited by Tsaritsa Eleonore of Bulgaria to Evksinograd, the royal residence near Varna, on the shore of the Black Sea. The presence of Queen Elisabeta was not approved by Tsar Ferdinand of Bulgaria, who demonstratively left the country. The visit to Evksinograd, in May 1911, can be considered without political and diplomatic value in the context of Romanian – Bulgarian relations. The presence of Queen Elisabeta in Evksinograd is the last journey of a Romanian sovereign to the territory of Bulgaria and, in general of a Romanian head of state to the South of the Danube for the following half century, when Prime Minister Petru Groza was invited, in 1947, by the communist leader of the new People’s Republic, Georgi Dimitrov. Research on Queen Elisabeta’s high-level state activities, analyses of the diplomatic and political relations in Southeast Europe and, in particular, between Romania and Bulgaria have given fleeting attention to this episode. It is rarely mentioned, and a more generous account of this stay at Evksinograd was not found.